Gelombang Elektromagnetik ELF : Inovasi Baru dalam Terapi Kesehatan Tulang - Rachmatul Hidayathika; Muhammad Nabil Makarim; Muhammad Irfan Andrianto; Ade Sudrajat; Diyajeng Luluk Karlina (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
Extremely Low Frequency (ELF) electromagnetic waves are increasingly recognized for their potential in treating bone health as a safe and effective non-invasive method. Studies have shown that ELF can stimulate osteoblast activity, increase bone density, and accelerate fracture healing. This article reviews the mechanism of ELF, its application in the treatment of osteoporosis, and its safety in clinical practice. With standardized parameters, ELF can be an innovative solution for chronic bone disorders or abnormalities, as well as providing great benefits in the medical world.